STRATEGI KEPALA SEKOLAH DALAM KEBIJAKAN PEMBELAJARAN PADA MASA PANDEMI COVID-19 - Ahmad Nashihin Agus Saputro; Abu Darim (Pedir Research Institut, 2022)
Strategy is an effort, program or plan of the principal in learning activities in the classroom and outside the classroom during the pandemic. School principals have an important position in determining policies and providing education during the Covid-19 pandemic. Policy is the attitude taken by the principal and becomes the basis of work in the educational environment he leads. The pandemic period is a period of spreading epidemic disease outbreaks caused by a new virus called sar cov-2. The research objectives are to find out: 1). Planning 2) Organizing 3) Implementation and 4) Supervision of school principals in learning policies during the Covid-19 pandemic. This type of research is a case study approach. Collecting data through observation, interviews and documentation. The validity of the data by means of triangulation. The results showed that the principal's strategy in learning policies during the Covid-19 pandemic at Maarif Jogosari Pandaan Elementary School, Pasuruan Regency went well with seven policies, namely: 1) Carrying out learning boldly 2) Forming a school Covid-19 Task Force 3) Using an emergency curriculum 4) Determination of Attendance Schedule for Educators and Education Personnel with a picket schedule 5) Removing extracurricular activities 6) Implementing limited face-to-face learning activities 7) Reducing education costs